2010
DOI: 10.1364/ol.35.000112
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond polarization-resolved laser-induced breakdown spectroscopy

Abstract: It is shown that the continuum emission produced in the ablation of an Al target with nanosecond laser pulses is much more strongly polarized than the discrete line emission. This effect may be utilized to improve the resolution of the laser-induced breakdown spectroscopy spectrum by using a polarizer to filter out the continuum background. The effects of laser fluence and focal position are also reported. It is further shown that the lifetime of the emission closely tracks the intensity spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…2 shows emission (LIBS) and polarization spectra over the range of 385-505 nm taken with a fluence of 13.2 J/cm 2 . These spectra are similar to our previous work [4] as well as that of Majd et al Specifically, the polarization of the continuum radiation varies slowly with wavelength in this spectral region. The strong Al lines near 400 nm in the LIBS spectrum appear as windows in the polarization spectrum, indicating that the polarization of the discrete emission is smaller than that of the continuum emission.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…2 shows emission (LIBS) and polarization spectra over the range of 385-505 nm taken with a fluence of 13.2 J/cm 2 . These spectra are similar to our previous work [4] as well as that of Majd et al Specifically, the polarization of the continuum radiation varies slowly with wavelength in this spectral region. The strong Al lines near 400 nm in the LIBS spectrum appear as windows in the polarization spectrum, indicating that the polarization of the discrete emission is smaller than that of the continuum emission.…”
supporting
confidence: 91%
“…At an angle of incidence of 30 o , the difference in the Fresnel reflection efficiencies of s-and p-polarization are small and could give rise to P b 10%. While this effect may explain the small polarizations seen in the experiment of Asgill et al, it cannot account for the very large polarizations seen in previous experiments [1][2][3][4][5], ranging from 20% to almost complete (P = 100%) polarization.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The methods used in the characterization of laserinduced plasma and shock waves include different optical techniques, such as shadow and streak photography [8][9][10][11], holography [12], laser-beam-deflection probe [13], interferometry [14], and laser-induced spectroscopy [15,16]. Since the plasma and ablative shocks are short, transient phenomena that exhibit significant pulse-topulse variations, there is a special interest in methods that provide their spatially and temporally resolved characterization [17].…”
mentioning
confidence: 99%
“…In several studies [19][20][21][22][23][24], strong polarization of LIP emission was reported for many materials. More recently, it was found that this effect is caused by Fresnel polarization of the reflected light rather than by an anisotropic electron velocity distribution [25].…”
Section: Introductionmentioning
confidence: 99%